2019
DOI: 10.3390/nano9091239
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Quicklime Nanocomposites Prepared Using a Nickel Catalyst Supported on Calcium Oxide Derived from Carbonate Stones

Abstract: Carbon nanotube-quicklime nanocomposites (CQNs) have been synthesized via the chemical vapor deposition (CVD) of n-hexane using a nickel metal catalyst supported on calcined carbonate stones at temperatures of 600–900 °C. The use of a Ni/CaO(10 wt%) catalyst required temperatures of at least 700 °C to obtain XRD peaks attributable to carbon nanotubes (CNTs). The CQNs prepared using a Ni/CaO catalyst of various Ni contents showed varying diameters and the remaining catalyst metal particles could still be observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…XRD and Raman characterizations were applied to check the compositions of the products, as shown in Figure 3. XRD result (Figure 3a) indicates that the peak at 26.4° belongs to (002) crystallographic planes of CNT [10,11,23], and other four peaks should be attributed to the (111), (110), (200), and (220) planes of the stainless steel substrate, respectively [10,11]. As shown in Figure 3b, the Raman spectrum shows three typical characteristic peaks of the CNTs, i.e., D band (1350 cm −1 ), G band (1585 cm −1 ), and G’ (2706 cm −1 ), respectively [11,24].…”
Section: Resultsmentioning
confidence: 99%
“…XRD and Raman characterizations were applied to check the compositions of the products, as shown in Figure 3. XRD result (Figure 3a) indicates that the peak at 26.4° belongs to (002) crystallographic planes of CNT [10,11,23], and other four peaks should be attributed to the (111), (110), (200), and (220) planes of the stainless steel substrate, respectively [10,11]. As shown in Figure 3b, the Raman spectrum shows three typical characteristic peaks of the CNTs, i.e., D band (1350 cm −1 ), G band (1585 cm −1 ), and G’ (2706 cm −1 ), respectively [11,24].…”
Section: Resultsmentioning
confidence: 99%
“…The G peak reflected sp 2 hybridization, a six-membered ring plane stretching and symmetrical vibration. The high-strength G peak reflected the high degree of graphitization of carbon materials [ 21 ]. The D peak caused by the edges or defects of the crystallite plane reflected the defect structure inside the materials.…”
Section: Resultsmentioning
confidence: 99%
“…The D peak caused by the edges or defects of the crystallite plane reflected the defect structure inside the materials. The peak height ratio of D and G peak I d / I g was 0.807, which indicated that MWCNTs had a higher degree of graphitization and a higher proportion of ordered structures [ 21 , 22 ]. The high degree of graphitization of MWCNTs benefited the bio-safety of this material [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once a steady flow of these building blocks is established, CNTs are assembled in a continuous, but decelerating fashion caused by gradual deactivation of the catalyst [83]. An assortment of synthetic feedstocks is used for the process, which involves diverse classes of chemical compounds such as hydrocarbons (both aliphatic [84][85][86][87] asnd aromatic [77,[88][89][90]), alcohols [91][92][93][94], ketones [95,96], ethers [97,98], amides [99], etc. These can either be in a gaseous state [86,87] or they are vaporized [91,92,98] before injection to the reactor.…”
Section: Cnt Synthesis Methodsmentioning
confidence: 99%